Study on the age and growth characteristics of Sepia esculenta in the East coast of China based on beak microstructure - Bilin Liu; Bilin Liu; Bilin Liu; Bilin Liu; Yuzhe Ou; Minhua Zhou; Hu Zhang; Yueyue Xiao; Kaiwei Zu; Chaowen Zhu; Haisheng Hu (Frontiers in Marine Science)
This study investigates the daily age and growth characteristics of Sepia esculenta along the East coast of China, aiming to provide essential data for population dynamics and sustainable fisheries management. A total of 360 specimens were collected from September to November 2021. Among these, 178 individuals (81 females and 97 males) were successfully aged by analyzing growth increments in the sagittal section of the upper beak rostrum (RSS) using beak microstructure analysis. The mantle length (ML) of S. esculenta ranged from 55 to 201 mm and body weight (BW) from 30 to 667 g, with no significant sex differences. Age estimates ranged from 59 to 152 days, averaging 106.44 ± 17.35 days for females and 103.86 ± 19.70 days for males. The ML-age relationship fitted a linear growth model, while BW-age relationships followed an exponential model for females and a power function model for males. Growth rate analysis showed varied growth trajectories with age, with the highest absolute growth rate (AGR) of ML observed at 120–150 days for females (1.23 mm/d) and at 60–90 days for males (1.93 mm/d). These findings provide crucial insights into the growth patterns and population dynamics of S. esculenta in the East coast of China, supporting resource assessment and sustainable management efforts.